(untitled) (Perioperaciina Medicina, 2019)
This article is devoted to the questions of infusion therapy – a method of treatment, which gives the possibility of parenteral administration of various substances and medicines into the body and directions for the promotion of basic functions and bio-chemical processes in the body. We considered the organization of conducting adequate infusion therapy in a particular patient, with a specific clinical situation, the questions of the purpose and tasks of infusion therapy now and in the future (tactics and strategy), the means that will be applied, their type, volume, quantitative and qualitative correlation, ways of introduction, speed and duration of the general and, if necessary, of the skin volumetric component, methods for controlling effectiveness and safety. In addition, the issues of physiological and pathological and physiological processes taking place in the child’s body and the justification of the use of different methods of infusion therapy for effective and safe infusion therapy in the child are considered.